ORIENTATION OF THE MOTIVATIONS TO PRACTICE PHYSICAL ACTIVITY IN NATURAL ENVIRONMENT - Granero-Gallegos, Antonio; Baena-Extremera, Antonio; Ruiz-Montero, Pedro Jesús; Baños, Raúl (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2018)
This paper analyses the relationships between the goal orientations and the hikers and cycle‑tourers’ motivations older than 15 have to practice physical-sport activity in natural environments in the context of the Way of Saint James. The investigation has been developed by administering a self-administered questionnaire to a sample of 1.071 individuals. After the factorial analysis, the results have shown the importance of the situation and the relationship between the intrinsic character of the motivations related to leisure, recreation, and affiliation, as well as to the escape and escape valve, and the task orientation. The ego orientation is less outstanding in the physical-sport and recreational activities in the natural environment, although these are aspects that are more important for women in this environment.